The Influence of Culture on Indonesian language in Elementary Schools in Tanjung Sarang Elang, Panai Hulu - Eka Nurbulan; Emi Juwita Saragi; Anwar; Abdurrahman Adisaputera; Khairil Ansari (PT Inovasi Pratama Internasional, 2024)
Indonesian is experiencing a period of accelerated development and modernization. This is evidenced by the growing vocabulary and stability of its structural elements. It is important to note that, alongside this process, the language is also facing challenges in terms of its continued development and usage. It is likely that many young people and the general public are still unaware of Indonesian's position and function in the context of the country's identity. They fail to recognize the role of Indonesian as a symbol of national pride, national identity, a means of communication between citizens, between regions, and between cultures, as well as a tool for unifying various ethnic groups with their respective socio-cultural and linguistic backgrounds into the unity of Indonesian nationality. Therefore, it is essential to continually develop the Indonesian language in order to advance the nation and state.